VD_FINDINFO HC / 2015 / 323 vom 3. März 2015 - VD Tribunal cantonal (2015)
MODÉRATION, OBLIGATION DE RENSEIGNER, HONORAIRES, AVOCAT, MOTIVATION DE LA DÉCISION | 394 al. 3 CO, 29 al. 2 Cst., 45 al. 1 LPAv, 45 LPAv, 51 LPAv, 48 LPA-VD